Cerebrospinal Fluid Markers of Neurodegeneration Associated with Postoperative Delirium in an Older Elective Arthroplasty Population. (20th December 2022) - Sweeney, Aoife; Passmore, Anthony Peter; Beverland, David; McGuinness, Bernadette; McAuley, Daniel F; Mawhinney, Tim; Schott, Jonathan M; Heslegrave, Amanda; Zetterberg, Henrik; Cunningham, Emma L
Abstract: Background: Postoperative delirium (POD) is associated with subsequent cognitive decline. It is not yet clear to what extent that is because delirium indicates underlying neurodegeneration. Method: An observational cohort study of POD in an elective arthroplasty population recruited 315 individuals. All participants were community‐dwelling adults aged over 65, without a diagnosis of dementia, undergoing hip or knee replacements. Cerebrospinal fluid (CSF) was sampled pre‐operatively at the time of spinal anaesthesia and delirium was assessed daily on days 1‐3 postoperatively. Stored CSF samples (n = 270) were analysed for markers of inflammation and neurodegeneration. Statistical analysis was carried out to determine associations of these CSF markers with POD. Result: Those who developed POD (n = 44) had significantly higher levels of CSF glial fibrillary acidic protein (GFAP; p=0.04), a marker of inflammation; CSF neurofilament light (NFL; p=0.04), a marker of axonal degeneration; and CSF triggering receptor expressed on myeloid cells 2 (sTREM2; p=0.02), a marker of age‐related neuroinflammation and tau‐related neurodegeneration and significantly lower levels of CSF amyloid‐beta 1‐42 (Aβ42; p=0.01) and CSF Aβ42/40 ratio (p=0.01) compared to participants who did not develop POD. Conclusion: Significantly higher levels of preoperative neurodegenerative CSF markers associated with dementia were found in those who developed POD following elective arthroplasty surgery. This suggests that people, without a pre‐existing diagnosis of dementia, who develop POD after elective arthroplasty surgery are more likely to have underlying neurodegeneration.